2021
DOI: 10.1002/ehf2.13660
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound in outpatients with heart failure: the wet‐to‐dry HF study

Abstract: AimsIn ambulatory patients with chronic heart failure (HF), congestion and decongestion assessment may be challenging. The aim of this study is to assess the value of lung ultrasound (LUS) in outpatients with HF in characterizing decompensation and recompensation, and in outcomes prediction. Methods and resultsHeart failure outpatients attended to establish HF decompensation were included. LUS was blindly performed at baseline (LUS1) and at clinical recompensation (LUS2). B-lines were counted in eight scanned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 39 publications
0
19
0
1
Order By: Relevance
“…Pulmonary congestion (PC) is one of the major characteristics of HF [ 6 , 7 , 8 ]. The importance of PC in the disease course of HF has been confirmed by numerous clinical trials, and the presence of PC is shown to be associated with a significantly increased risk of mortality and rehospitalization in HF patients [ 6 , 9 ]. Multiple studies have demonstrated the usefulness of assessment of pulmonary congestion from a prognostic point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary congestion (PC) is one of the major characteristics of HF [ 6 , 7 , 8 ]. The importance of PC in the disease course of HF has been confirmed by numerous clinical trials, and the presence of PC is shown to be associated with a significantly increased risk of mortality and rehospitalization in HF patients [ 6 , 9 ]. Multiple studies have demonstrated the usefulness of assessment of pulmonary congestion from a prognostic point of view.…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic significance of the number of B-lines varied across studies. Most studies indicated that a sum of ≥5 B-lines was associated with a higher probability of 12-month all-cause death, and ≥15 B-lines with higher probability of HF readmission [45,[50][51][52]56,61,65]. Others [57] suggested that the presence of 30-40 B-lines at admission was a risk factor for readmission or mortality, and the presence of ≥15 B-lines could indicate just an increased risk of persistent pulmonary congestion.…”
Section: Resultsmentioning
confidence: 99%
“…In der ambulanten Versorgung von Patienten mit chronischer Herzinsuffizienz
chronischer Herzinsuffizienz
zeigt LUS eine prognostische Bedeutung für den Tod und eine herzinsuffizienzbedingte Hospitalisierung sowohl nach 30 Tagen wie auch nach 32 Monaten. Hierbei korreliert die Anzahl der B‑Linien in einem 8‑Zonen-Protokoll mit einer erhöhten Mortalität [ 30 , 31 ].…”
Section: Lungensonographie In Der Ambulanten Versorgungunclassified